PENGARUH BRAND POSITIONING WONDERFUL INDONESIA TERHADAP KEPUTUSAN WISATAWAN MANCANEGARA UNTUK BERKUNJUNG KE INDONESIA (Survei Terhadap Wisatawan Mancanegara Asal Singapore, Malaysia dan Australia) - Maharani P, Conny; Andrianto, Tomy (THE Journal : Tourism and Hospitality Essentials Journal, 2014)
In the current era of the world globalization, tourism is one of the sectors that contributed substantially in the development and growth of each country, including Indonesia. Indonesia is a country that is very rich in natural and cultural resources. That was one factor Indonesia became the one of attractive destinations for tourists, especially foreign tourists. In increasing the number of tourist arrivals to come to Indonesia, the Ministry of Tourism and Creative Economy as a government agency in the field of tourism using a variety of strategies, and the which one is branding. This is done to strengthen the image of Indonesian tourism minds of the tourists, particularly in promoting the growth and the number of tourist arrivals in accordance with the targets to be achieved. Brand Positioning became one planned strategy associated with the repositioning of the brand Visit Indonesia Year to be Wonderful Indonesia. This is done for brand dissemination Wonderful Indonesia be easily attached to the minds of the desired target market, especially foreign tourists who’s coming to Indonesia. Brand positioning is a way to demonstrate the superiority of a brand and how it differs from other competitors. There are five dimensions that can diigunakan to see the positioning of the brand by AB Susanto and Hilmawan W (2004:154), namely the value, uniqueness, credibility, sustainability, and suitability. This study aims to determine the implementation of brand positioning and influence the decision of foreign tourist to make decision to visit. Objects in this study is represented by foreign tourists from top three countries in the number of foreign tourists visiting Indonesia, namely Singapore, Malaysia and Australia. The independent variable in this study is the brand positioning (X). The dependent variable in this study is the decision to visit (Y). The method used in this research is descriptive and verificative methods. The method used is explanatory survey and cross sectional approach. Samples taken were 100 respondents were divided into three categories namely 39 respondents origin Singapore, 33 respondents from Malaysia and 28 respondents from Australia with sample technique used is stratified random sampling. While the data analysis techniques used are simple linear regression analysis using SPSS 17.0 for Windows. The results showed that the brand positioning has a significant influence on the decision of foreign tourists to visit Indonesia. As for suggestions for Kemparekraf is optimizing and developing marketing brand Wonderful Indonesia to be more widely known and more deeply so as to motivate more and more foreign tourists to come to Indonesia.